Tremor Suppression Using Smart Textile Fibre Systems (Journal of Fiber Bioengineering and Informatics, 2018)
This research deals with a non-invasive system that can be used to harvest waste mechanicalenergy and utilise this energy to suppress tremors. Hand tremors can emanate from medical conditionssuch as Parkinson disease and Arthritis. These tremors can be distinguished from other vibrations due tothe associated frequency spectra. Mechanical signals are picked up by piezoelectric sensors before thegenerated voltage is filtered, converted and stored, or used directly to suppress the tremor. Two systemlevel methods used for the suppression of tremor are discussed. As the device is proposed for glovestructures, material flexibility is of key significance thus not hindering the bearer's motor functions.Conventional piezoelectric ceramic materials are recognised for their high piezoelectric coefficientsin comparison to flexible piezoelectric polymer films. However, ceramic materials are rigid, heavyand offer limited opportunities for forming and shaping. Ceramic based piezoelectric materials in finefibre form across a range of diameters (10-250&#956m) were used in this research. When integrated intocomposite structures the resulting materials retained all the qualities of bulk piezoelectric ceramics(electrical, mechanical, chemical) and mitigated the disadvantages of weight and brittleness. Variouspiezoelectric fibre composites and piezoelectric polymer film structures were compared, and thepotential for their exploitation in glove based power harvesting and tremor suppression structuresassessed.
Keywords: piezoelectricity; energy harvesting; vibration suppression; piezoelectric fiber composites; wearable; synchronized switched harvesting on inductor; active vibration control